A literature review of clinical outcomes associated with antipsychotic medication use in North American nursing home residents. Issue 6 (June 2015) - Chiu, Yunwen; Bero, Lisa; Hessol, Nancy A.; Lexchin, Joel; Harrington, Charlene
Highlights: A review of antipsychotic medication use in nursing home residents. Antipsychotic medication use resulted in many adverse outcomes. Efficacy is mixed depending on the type of antipsychotic medication and regimen. Studies subsidized by industry funding showed favorable outcomes. Non-pharmacological options are recommended to reduce antipsychotic medication use. Abstract: The benefits and harms of antipsychotic medication (APM) use in nursing home residents need to be examined because, although commonly used, APMs are considered an off-label use by the Food and Drug Administration for residents with dementia and behavioral problems. The objective of this study was to provide a realist literature review, summarizing original research studies on the clinical effects of conventional and atypical APM use in nursing home residents. Searches of multiple databases identified 424 potentially relevant research articles, of which 25 met the inclusion criteria. Antipsychotic medication use in nursing home residents was found to have variable efficacy when used off-label with an increased risk of many adverse events, including mortality, hip fractures, thrombotic events, cardiovascular events and hospitalizations. Findings suggested certain APM dosing regimens (e.g. fixed-dose) and shorter duration of use might have fewer adverse events. Non-pharmacological interventions should still be considered the first-line treatment option for nursing home residents with dementia related behavioral disturbances, as more studies are needed to establish safer criteria for APM use in nursing homes residents.